Characterising South Africa’s major dust sources - Bekiswa, Sisanda Ongeziwe (Department of Environmental and Geographical Science, 2020)
The study investigates the surface controls of major dust emissions and determines the patial distribution of major dust source in South Africa. This study follows a multi-disciplinary approach where primary and secondary data were used. The main objective of the study is to determine the spatial distribution of South Africa's Major Dust Sources. Meteosat Second Generation (MSG) satellite imagery, land use and land cover maps were used to achieve the first and the second objectives of the study. Primary data involved sampling 30 soil samples in the field in order to achieve the third objective of the study. The crust, soil moisture, soil texture and grain size are all controls of dust emission. This investigation is however focused predominantly on grain size characteristics. GIS methods were also used to determine soil type from the African soil map. Soil samples in both provinces were then collected to assess the Particle Size Distribution (PSD) of the soils. The particle size was determined based on a sieve analysis for grain sizes that were greater than 2mm and laser diffractometry, MasterSizer (Malvern) was used to achieve this. The results from the Malvern were later put to R Statistics where they were clustered into eight clusters to determine similarities and difference of the grain size. Because there is no uniqueness in the soil types found in the study area, there were no solid conclusions made based in them. The results show that the soil types are found across South Africa but not the same amount of dust activity was detected in the other parts of the country. Previous studies show that global significant dust sources are natural sources such as lakes, pans and depressions. However, results demonstrate that South African dust sources are anthropogenic sources resulting from commercial agriculture in semi-arid regions. This study has demonstrated that surface sediments suitable for dust production are a mixture of fine material, silt (50µm) and coarse material, sand (2000µm) and it appears that all clusters in this study all contained both mixtures and all have potential to emit dust.